Doenças tropicais negligenciadas: uma nova era de desafios e oportunidades - Dias,Luiz C. (2013)
In an article recently published in Química Nova, entitled "Chemistry Without Borders" ("Química Sem Fronteiras") [Pinto, A. C.; Zucco, C.; Galembeck, F.; Andrade, J. B.; Vieira, P. C. Quim. Nova 2012, 35, 2092], the authors highlighted the important aspects of science and technology with special emphasis on the field of Chemistry and its contributions toward a more prosperous Brazil of future. As a second step in that direction, this article extends the discussion of a key issue for the country in the framework of the chemistry community through the so called position papers in strategic areas. This document is a part of the contribution of the Brazilian Chemical Society to the World Science Forum to be held in Rio de Janeiro in November 2013. In this context, the present paper provides a brief discussion on neglected tropical diseases (NTDs) with emphasis on the current challenges and opportunities towards the development and evolution of the field. NTDs leads to illness, long-term disability or death, and has severe social, economic and psychological consequences for millions of men, women, and children worldwide. In most cases, the available treatments are inadequate and extremely limited in terms of efficacy and safety, leading to an urgent demand for new drugs. In addition to the traditional challenges involved in any drug discovery process, it is widely recognized that there is an innovation gap and a lack of investment for research and development (R&D) in the area of NTDs. In the last few decades, methods toward combating, eradication, prevention, and treatment of NTDs have been repeatedly emphasized in the major international agendas. Developments in these strategies and alliances have continued to have an essential impact, particularly in the area of drug discovery, both in Brazil and globally and should be encouraged and supported. Several examples of international activities dedicated to the reduction of the devastating global impact of NTDs can be provided. Despite the beneficial developments in the past 30 years, NTDs continue to devastate poor communities in remote and vulnerable areas, in large part, due to market failures and public policies. Recent studies have shown that among 756 new drugs approved between 2000 and 2011, only four new chemical entities (NCEs) were identified for the treatment of malaria, while none were developed against NTDs or tuberculosis. Furthermore, only 1.4% of approximately 150,000 clinical trials were registered for neglected diseases, with a smaller number of trials for NCEs. Establishment and strengthening of global strategies involving the triad "government-academia-industry" is fundamental to the success in R&D of new drugs for NTDs. National and international public-private initiatives that aim to create, encourage, and invest in R&D projects have been implemented and therefore are of utmost importance to successfully integrate Brazil into this new paradigm. It is essential to lay the foundation for mechanisms that will intensify investments in infrastructure, training, and qualification of personnel with an ultimate strategic vision that foresees continuity. Our research group has made significant contributions to the development of this field with the goal of forging new frontiers while tackling both current and future challenges that include indispensable elements such as innovation and integration.